2016
DOI: 10.1038/aps.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid prevents LPS-induced up-regulation of PDE4B and stimulates the cAMP/CREB signaling pathway in PC12 cells

Abstract: Aim: Phosphodiesterase 4 (PDE4) isozymes are involved in different functions, depending on their patterns of distribution in the brain. The PDE4 subtypes are distributed in different inflammatory cells, and appear to be important regulators of inflammatory processes. In this study we examined the effects of ferulic acid (FA), a plant component with strong anti-oxidant and anti-inflammatory activities, on lipopolysaccharide (LPS)-induced up-regulation of phosphodiesterase 4B (PDE4B) in PC12 cells, which in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…dose-dependent prevention from LPS-induced upregulation of 3′5′-cyclic nucleotide phosphodiesterase 4B, reversion of the LPS-induced downregulation of CREB and pCREB (stimulation the cAMP/CREB signaling pathway) in PC12 cells [ 20 ].…”
Section: Figurementioning
confidence: 99%
“…dose-dependent prevention from LPS-induced upregulation of 3′5′-cyclic nucleotide phosphodiesterase 4B, reversion of the LPS-induced downregulation of CREB and pCREB (stimulation the cAMP/CREB signaling pathway) in PC12 cells [ 20 ].…”
Section: Figurementioning
confidence: 99%
“…In this study, the cellular mechanism of ATEO against oxidative stress was investigated. PC12 cells were selected as the cell model due to their phenotypic characteristics of sympathetic neurons [25,26]. We evaluated whether ATEO had a beneficial effect on H 2 O 2 -stressed PC12 cells, including a PGC-1α-mediated increase of cell viability, decrease of ROS level, and upregulation of antioxidant protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the cAMP-PKA-CREB-BDNF signaling pathway is closely related to depression ( Wang et al, 2017 ; Ye et al, 2017 ). Meanwhile, the related proteins in the cAMP-PKA-CREB-BDNF signaling pathway can also improve myocardial microcirculation, improve the ability of myocardial cells to resist ischemia and hypoxia, and effectively prevent the development and deterioration of CHD ( Huang et al, 2016 ). To verify whether XPF works in treating CHD with depression by intervening in the cAMP-PKA-CREB-BDNF signaling pathway and cell apoptosis process, the expression of 5-HT, Ang-II, cAMP, PKA, CREB, BDNF, Bcl-2, Bax, Cyt-c, and caspase-3 in the myocardial and hippocampal tissues were detected.…”
Section: Resultsmentioning
confidence: 99%